Salvaguarda cultural para la preservación y promoción del carnaval de Guamote, provincia de Chimborazo, año 2025. - Chicaiza Carguachi, Mario Fernando (2025)
The current project focuses on Cultural Safeguarding for the Preservation and Promotion of the Guamote Carnival, Chimborazo Province, 2025. It addresses the need to protect and revitalize one of the most representative manifestations of Guamote's intangible cultural heritage. The overall objective of the study is to design a comprehensive cultural safeguarding plan to ensure the preservation, revitalization, and promotion of this festival for the Guamote population. To achieve this, the research focused on three specific objectives: the first was to identify and document the various intangible cultural elements that comprise the carnival, highlighting their uniqueness and value. It was evident that the festival is a center of social cohesion, uniting the local population and migrants through practices such as priostazgo, jochas, coplas, native attire, the carnival burial, and the Guamoteña intercultural parade. Secondly, the factors threatening the continuity of the Guamote carnival were analyzed in detail, identifying significant challenges such as the lack of interest of younger generations, lack of resources, declining community participation, and the alteration of traditional elements due to external influences. Finally, based on these findings, a cultural safeguarding plan was proposed, based on essential policies aimed at intergenerational transmission, exhaustive heritage documentation, the strategic promotion of the carnival as a cultural tourism attraction, and the active participation of the population, government institutions, and cultural organizations to ensure the continuity and recognition of this invaluable cultural legacy for present and future generations, strengthening local identity and promoting tourism development in the Guamote canton.